O-218 Single-cell RNA sequencing reveals that Ashermańs syndrome is caused by chronic inflammation that induces differential molecular and cellular cartography in the human endometrium. (30th June 2022) - Santamaria Costa, X; Beatriz, R; Nanda, K; Estefania, F; Raul, P; David, V; Luciano, R; Sergi, Q; Juan José, T; Ramon, A; Julio, H; Inmaculada, M; et al.
Abstract: Study question: What is the differential cellular, transcriptomic and immunological differences of the human endometrium in AS versus healthy patients at single cell resolution? Summary answer: The epithelial fraction is decreased, the myeloid and lymphoid cell lineages increased with an altered inflammation, inhibition of angiogenesis and EM abnormal remodeling. What is known already: Asherman's Syndrome (AS) is an acquired pathological condition, defined by the presence of intrauterine adhesions (IUAs) causing the uterine walls to adhere to one another resulting in menstrual abnormalities, pelvic pain, infertility, recurrent miscarriage, and abnormal placentation. However, the underlaying cellular, transcriptomic and immunological mechanisms at the single-cell level that occur in AS have not been investigated. Study design, size, duration: Single cell RNA-seq (scRNA-seq) was performed on 41, 854 cells corresponding to endometrial biopsies from a total of 7 individuals with severe AS (AFS classification 1998). These patients were involved in a phase I/II, prospective, non-randomized, uncontrolled, multicenter, interventional clinical trial authorized by the Spanish Medicines Agency (AEMPS)(2016-003973-23). Control healthy endometrium was represented by 68, 026 cell transcriptomes from our previous work (Wang et al. 2020). Participants/materials, setting, methods: Seven patients were included. Ultrasound and hysteroscopies were performed in mid secretory phase. Endometrial specimens were digested with collagenase and filtered. Epithelial cells were digested with trypsin and red blood cells removed. After MACS live enrichment, cells were loaded onto ChromiumNext GEM (10xGenomics). Libraries were sequenced in a Novaseq, and reads processed with CellRanger. Quality filtering, normalization, clustering and differential expression analysis were applied from 'Seurat' package. Functional enrichment analysis was computed using 'escape' package. Main results and the role of chance: In total 109, 880 cell transcriptomes were compared and found changes in cell population ratios in two specific cell types. First, the epithelial fraction was decreased in AS compared to healthy condition (26.53% vs 45.7%, respectively) specifically the epithelium representing the opening of the window of implantation (WOI) (0.25% vs 2.01%respectively), and the ciliated epithelium (0.84% vs 6.12%, respectively). Second, the myeloid and lymphoid cell lineages, which are much more abundant in AS samples. Macrophages (1.97% vs 0.24%, respectively), CD8+ T cells (3.71% vs 1.34%, respectively), and CD8- T cells (2.28% vs 0.55%, respectively). In addition, there was a different transcriptomic composition represented by three differential linked clusters related to AS condition. First, a unique stromal cluster labelled as stromal_ACTA2 that express genes related to contractile functions (ACTA2, MYH11, DES). Second, a specific AS epithelium cluster closely related to antigen processing and presentation of HLA class II family genes. Third, a KRT8 ACTA2 cluster composed by genes related to collagen (COL3A1 and COL1A1) and IGFBP5. Enrichment analysis performed with ssGSEA revealed the functional impact of the AS condition identifying an increase in different GO terms related to tissue damage, pro-inflammatory processes, inhibition of angiogenesis. Limitations, reasons for caution: Despite these promising results, this is an study in progress to be completed with 10 patients Wider implications of the findings: These findings describe for the first time the pathophysiology of AS at single cell level with the functional involvement of inflammation, fibrosis, and defective angiogenesis in this pathological condition. Trial registration number: Eudra CT 2016-003975-23